New practical approach and basic considerations for a better energy conversion in a permanent magnet motor. (March 2019) - Aguirre, M.; Muñoz, V.; Alcolea, A.
Highlights: A force gauge allows to measure the real interactive magnetic force between pairs. Magnetic saturation curves enables to know the best energy conversion efficiency. Geometry of the magnetic parts involved is critical in an efficient magnetic design. Abstract: This paper presents a new practical approach to analyze how efficient the force lines of a magnetic field are in an assemblage electromagnet–permanent magnet of an electric motor while in operation. For this purpose, we tested a combination of neodymium-based magnets of different geometries and pull forces, along with homemade electromagnets of a variety of core materials, designed to achieve the highest energetic efficiency. The experiments—monitored with a force gauge—let us to determine the interactive force, so as to eventually build the magnetic saturation curves for every scenario. The compositional and structural study by energy dispersive spectroscopy (EDX) and X-ray diffraction (XRD) helped to understand the electromagnetic response of the materials involved. We demonstrated that shape and size of the magnetic parts concerned—together with the magnetic saturation and energy consumption—are critical aspects to consider in an efficient magnetic design.